AN ANALYSIS OF LANGUAGE CODE THAT USED BY PEOPLE AT BLACKBERRY MESSENGER’S STATUS - Agus Triyogo (Jurnal Perspektif Pendidikan, 2016)
The aims of this research is to describe kinds of language code that used by people in their daily life. This research is categorized as a qualitative research that focuses in naturalistic study. In collecting the data research, the writer was monitoring on Blackbarry mesanger’s status. The result at this research show that status on blackbarry messenger grouped in three parts, they are code mixing, code switching, and Borrowing language. The first group is Code mixing’s status, it devided become three categories, they are Insertation, alternation, and congruent lexicalization. The insertation found five status wherein two status mixing in English and Java. One statuses categories in congruent lexicalization and one statuses categoies in alternation. The second group is Code switching, the status devided in three types, they are : three statuses include Intra-sentential switching, one status include taq- switching, three statuses include Inter-sentential switching. And the last group is borrowing language.